2020
DOI: 10.1038/s41541-020-0174-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of FLU-v, a broad-spectrum influenza vaccine, in a randomized phase IIb human influenza challenge study

Abstract: FLU-v, developed by PepTcell (SEEK), is a peptide vaccine aiming to provide a broadly protective cellular immune response against influenza A and B. A randomized, double-blind, placebo-controlled, single-center, phase IIb efficacy and safety trial was conducted. One hundred and fifty-three healthy individuals 18-55 years of age were randomized to receive one or two doses of adjuvanted FLU-v or adjuvanted placebo subcutaneously on days −43 and −22, prior to intranasal challenge on day 0 with the A/California/04… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 40 publications
1
41
0
3
Order By: Relevance
“…Flu-V is a multi-epitope peptide vaccine comprising 4 peptides representing CD8+ T-cell epitopes originating from conserved regions in internal proteins M1, NPA, NPB and M2 from influenza A and influenza B. A single dose of FLU-v with adjuvant Montanide ISA 51 led to a significant reduction in the number of influenza symptoms in 40% of participants when compared to those receiving placebo (64.3%) [ 54 ]. M-001 is a DNA vaccine carrying nine conserved genes encoding B- and T-cell epitopes from the HA (four B and one CD4+ T-cell epitopes), NP (Two CD8+ and one CD4+ T-cell epitope), and M1 (one peptide that contains both B and CTL epitope) proteins of both influenza type A and type B strains.…”
Section: Design Of Multi-epitope Peptide-based Vaccinesmentioning
confidence: 99%
“…Flu-V is a multi-epitope peptide vaccine comprising 4 peptides representing CD8+ T-cell epitopes originating from conserved regions in internal proteins M1, NPA, NPB and M2 from influenza A and influenza B. A single dose of FLU-v with adjuvant Montanide ISA 51 led to a significant reduction in the number of influenza symptoms in 40% of participants when compared to those receiving placebo (64.3%) [ 54 ]. M-001 is a DNA vaccine carrying nine conserved genes encoding B- and T-cell epitopes from the HA (four B and one CD4+ T-cell epitopes), NP (Two CD8+ and one CD4+ T-cell epitope), and M1 (one peptide that contains both B and CTL epitope) proteins of both influenza type A and type B strains.…”
Section: Design Of Multi-epitope Peptide-based Vaccinesmentioning
confidence: 99%
“…Equimolar combination of four peptides (M1: DLEALMEWLKTRPILSPLTKGILGFVFTLTVP, NPA: DLIFLARSALILRGSVAHKSC, NPB: PGIADIEDLTLLARSMVVVRP, and M2: IIGILHLILWILDRLFFKCIYRLF) were tested in clinical trials and the safety and efficacy were reported. This suggested that FLU-v-like peptides activate the T cell arm of immune response and have potential as vaccines [ 163 , 164 , 190 ]. Multimeric-001 (M-001) is another peptide vaccine that has met its primary endpoint in phase II.…”
Section: Influenzamentioning
confidence: 99%
“…In turn, FLU-v, developed by PepTcell (SEEK), is a peptide vaccine comprised of four synthetic peptides with conserved epitopes from influenza A and B strains designed to provide a broadly protective cellular immune response against influenza A and B. Results from phase IIb clinical trials showed that adjuvanted FLU-v recipients ( n = 40) were significantly less likely to develop mild to moderate influenza disease (MMID) following intranasal challenge of A/CA04/H1N1 vs. placebo ( n = 42) (32.5 vs. 54.8% p = 0.035) [ 69 , 70 , 71 ]. Nevertheless, overall the vaccine protection effect was poor.…”
Section: Novel Universal Influenza Vaccinesmentioning
confidence: 99%